An H-system for a revolution surface without boundary - P. Amster; P. De Nápoli; M. C. Mariani (Abstract and Applied Analysis)
We study the existence of solutions an H-system for a revolution surface without boundary for H depending on the radius f. Under suitable conditions we prove that the existence of a solution is equivalent to the solvability of a scalar equation N(a)=L/2, where N:𝒜⊂ℝ+→ℝ is a function depending on H. Moreover, using the method of upper and lower solutions we prove existence results for some particular examples. In particular, applying a diagonal argument we prove the existence of unbounded surfaces with prescribed H.